(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Enthusiasm for AI applications that have enabled, among others, major advances in environmental protection has traditionally not been matched by adequate consideration of related environmental costs. The paper traces the European approach in this regard, dwelling on the EU AI Act (and beyond), to highlight its limits and opportunities in support of sustainable artificial intelligence.